Analysis of Human Capital Readiness and Digital Culture on Employee Performance in Facing Industry 4.0 : Case Study of Perum DAMRI - Febriani, Nabila Eka; Febriansyah, Hary (Paradoks : Jurnal Ilmu Ekonomi, 2024)
Perum DAMRI, a state-owned transportation company, faces significant challenges in transitioning to Industry 4.0, with only 4.7% of employees classified as digitally skilled. This condition indicates that Perum DAMRI needs to significantly improve human capital readiness to compete in the digital era. This study aims to evaluate the human capital readiness and digital culture, towards employee performance at Perum DAMRI Head Office in facing Industry 4.0 challenges.. A survey was conducted to assess human capital readiness and the influence of digital culture on performance. The findings indicate that human capital readiness, particularly in the knowledge and hard skills dimensions, is categorized as “Not Ready,” highlighting substantial gaps and the need for comprehensive training and development programs. Additionally, digital culture positively influences employee performance, emphasizing the importance of fostering values such as innovation, collaboration, agility, and a digital-first mindset. The study concludes that both human capital readiness and digital culture significantly affect employee performance, underscoring their critical roles in supporting DAMRI's transition to Industry 4.0.